Effect of total asset turnover, current ratio and debt to equity ratio on dividend payout ratio in company sector consumption goods industry sector companies listed on the Indonesia stock exchange period 2015-2017 - Dina Yara (Enrichment : Journal of Management, 2023)
The object of this research is to analyze the influence of total asset turnover, current ratio and debt to equity ratio on dividen payout ratio in sector consumer goods industry listed in Indonesian Stock Exchange with period of 2015-2017 partially or simultaneouly. This research uses quantitative descriptive research. The population of this research are 37 companies and the number of sample is 15 companies. The results research of F test (simultaneous) showed that there is a significant influence between total asset turnover, current ratio and debt to equity ratio on dividen payout ratio in sctor consumer goods industry listed in Indonesian Stock Exchange with the period of 2015-2017. The result research of t test (partial) showed that there is a significant influence total asset turnover on dividen payout ratio in sector consumer goods industry listed in Indonesian Stock Exchange with period of 2015-2017